Peran Podcast dalam Meningkatkan Aksesibilitas Informasi Keagamaan di Kalangan Gen Z - Siti Sofiah Rahmawati; Muhammad Miftahur Rahmat Isnaini; Canra Krisna Jaya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to explore the role of podcasts in increasing the accessibility of religious information among Generation Z (Gen Z) in Indonesia. Gen Z, who were born in the digital era, have unique characteristics as